EVALUATION OF SEKOLAH ISLAM TERPADU (SIT) ALIYA BOGOR BUILDING STRUCTURE SYSTEM BASED ON THE REQUIREMENTS OF SNI 2847:2019 - Lutfi, Muhamad; Mulyadi, Ersa Bestari (Universitas Ibn Khaldun Bogor, 2021)
Sekolah Islam Terpadu (SIT) Aliya Bogor is located in west Bogor district, Bogor city, West Java, was founded in 200, thus the standards used by planning consultant in building planning using old standard, where these standards have been updated with current standard, namely SNI 2847:2019. The evaluation carried out in this study based on requirements SNI 2847:2019 knowing the outcome of building that was said to be safe used help software ETABS) and SpColumn. Length of building of Umar Bin Khatab A and B are 18,60 meter;23,65 meter.Building area of building Umar Bin Khatab A and B are 541,26 m2; 865,59 m2. Concrete quality assessment (fc') that came from the test of hammer test column elements, beam elements, and plate elements as big 23,74 Mpa;26,59 Mpa;26,59 Mpa. After analysis some of to experience overstrength. The original column dimension In Building of Umar Bin Khatab A was K25x25 with shear reinforcement is í˜16-150 enlarge to K40x40 with shear reinforcement is í˜39-150 and beam dimension 20x40 enlarge to 35x55. On the building of Umar Bin Khatab B was K25x25 with shear reinforcement í˜16-150 enlarge to K40x40 with shear reinforcement í˜25-150, with the original beam dimension 20x40 enlarge to 30x55. The cost budget in the building of Umar Bin Khatab A is Rp 74.158.600,00 and in building of Umar Bin Khatab B is Rp 61.084.600,00.